Prediction Of Asthma Symptom Burden In Subjects Dispensed Low/Moderate Dose Fluticasone Propionate/Salmeterol (FSC) or Moderate/High Dose Fluticasone Propionate (FP) in Subjects Without History of ICS Use - Stanford, R.H.; Riedel, A.; Burke, J.; Borah, B.; Kulakodlu, M. (Journal of allergy and clinical immunology, 2010)
To estimate the frequency of asthma symptoms among managed care enrollees newly prescribed low/moderate dose fluticasone propionate/salmeterol (FSC) or moderate/high dose fluticasone propionate (FP) with no prior claims of inhaled corticosteroids (ICS) within 3 years.